Outdoor smoking in Nigeria: prevalence, correlates and predictors - Victor Lasebikan; Tiwatayo Lasebikan; Samson Adepoju (BMC, 2019)
Abstract Background There is a lack of data on smoking in outdoor-open bars in Nigeria that may translate into effective legislation on public smoking. Method This study determined the prevalence, demographic and clinical correlates as well as predictors of smoking among a community sample of 1119 patrons of open place bars in Ibadan, Nigeria. Data on current smoking was obtained using the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST), while smoking intensity was calculated using the Pack-Year. Prevalence of alcohol use was determined using the Alcohol Use Disorders Identification Test (AUDIT), while depression was diagnosed using the Mini International Neuropsychiatry Interview (MINI). Analysis was carried out by SPSS version 20.0 software using Chi square statistics, t test and ANOVA, and was set at 95% confidence interval. Results Prevalence of current smoking was 63.8% and the mean pack years of smoking of all respondents was 19.38 ± 17.16 years. Predictors of outdoor smoking were depression OR = 1.41, 95% CI (1.09-1.83) and alcohol use OR = 2.12, 95% CI (1.44-3.13). Predictors of high pack years were depression OR = 1.47, 95% CI (1.08-2.01), being married, OR = 1.78, 95% CI (1.29-2.45), high income, OR = 1.95, 95% CI (1.42-2.68) and alcohol use OR = 2.82, 95% CI (1.51-5.27). There was no significant relationship between stage of readiness to quit smoking and mean pack years of smoking, F = 0.3, p = 0.5. Conclusion The high prevalence of outdoor smoking in the sample calls for urgent public health initiatives for intervention. Thus, outdoor bars are potential tobacco use intervention sites to minimize the health consequences of smoking.